Ultrasensitive Terahertz Imaging Sensors Based on the Strong Coupling of Surface Phonon Polariton and Graphene Surface Plasmon Polariton - Jiaqi Zhu; Banxian Ruan; Qi You; Leiming Wu; Houzhi Cai; Xiaoyu Dai; Yuanjiang Xiang (IEEE Photonics Journal)
Surface plasmon polaritons (SPPs) with noble metals lose the capacity to confine the optical field in the long wavelength region, while surface phonon polaritons (SPhPs) in polar dielectrics show greater ability to achieve high local field, sub-diffraction confinement, and low optical losses in the mid-IR to THz spectral ranges. We propose a hybrid structure based on SPhPs mode with CsI and SPPs mode with graphene in THz spectral ranges. The characteristics of the coupling of these two modes have been analyzed and strong coupling has been confirmed theoretically. The results are applied to an intensity-interrogated terahertz sensor; the highest imaging sensitivity as high as 954 RIU−1 and a large figure of merit of 74 740 RIU−1 have been demonstrated. The results could find potential applications in gas detection in the THz band.